INFORMATION AND COMMUNICATION TECHNOLOGIES IN PHYSICS LESSONS - Irmatov, Fozil; Mamatkulov, Bahodir; Xasanboyev, Bakhtiyor; Pirmatov, Sarvar (Физико-технологического образование, 2021)
The article discusses the problem of improving the effectiveness of training in physics lessons, the direction of ICT application in lessons, extracurricular activities, research projects, about the skills that a teacher must possess in order to successfully use ICT